Pharmaceutical services in primary health care: dissatisfaction among users, managers and pharmacists - Manuela Martins Cruz; Karla Oliveira dos Santos Cassaro Heringer; Cristiane Lyrio; Girlandia Alexandre Brasil; Ewelyne Miranda de Lima; Denise Coutinho Endringer; Dominik Lenz; Ana Maria Bartels Rezende; Tadeu Uggere de Andrade (Universidade de São Paulo, 2022)
Abstract To assess the performance indicators for pharmaceutical services (PS) in primary health care (PHC), the level of satisfaction with pharmacy services among users and managers / pharmacists' impressions in relation to the findings were evaluated. The study used mixed methods, including a retrospective and descriptive study of the performance indicators for PS in PHC, an observational study on the level of satisfaction and a qualitative study of users' perception of pharmacy services at Health Units. Managers and pharmacists' impressions of the study results were also collected. Only 44.4% of pharmacies had a full-time pharmacist. From the establishments visited, 5.3% did not have an air-conditioned environment, and only 33.3% of the items essential to the Good Practices of Storage of Medicines and Supplies criteria were fulfilled. Although 77.9% of the prescribed medicines were dispensed, it did not reach the 80% standard. The satisfaction level of users was 3.2±0.6, indicating dissatisfaction with pharmacies' services. By means of an evaluation of each item within the questionnaire, it was possible to observe that variables related to pharmaceutical care presented low scores in relation to other domains, thus evidencing the fragility of the pharmaceutical- patient relationship in users' perception. Managers and pharmacists suggested that these results were related to the inadequate physical infrastructure of pharmacies, work overload, lack of recognition and undervaluation of pharmacists, lack of interaction within the PHC team, high turnover of pharmacists, and lack of PS prioritization by the administration. PS in PHC has structural and organizational weaknesses that require changes. In general, users are dissatisfied with pharmacies' services, especially with pharmaceutical care.